Pemanfaatan Kecerdasan Buatan sebagai Media Pendukung Pembelajaran bagi Guru SMK Gamaliel 2 Kota Madiun - Budisaputro, Crismantoro; Agustinus Kusdwiadji; Alim Citra Aria Bima; Moch Yusuf Asyhari (Asosiasi Riset Ilmu Teknik Indonesia, 2026)
One of the rapidly advancing Artificial Intelligence (AI) technologies is ChatGPT, an AI-based system capable of generating interactive text responses based on user prompts. Despite its potential to support teaching and learning activities, the utilization of AI technology at Gamaliel 2 Vocational High School (SMK Gamaliel 2), Madiun City, remains limited. Many teachers have not yet optimally adopted AI-based applications due to limited knowledge, skills, and experience in using such technologies. To address this issue, a training program was conducted to improve teachers' digital literacy and competence in utilizing AI as a learning support tool. This community service activity aimed to introduce the ChatGPT platform as an AI-based learning support tool for teachers. The training methods consisted of lectures, discussions, hands-on practice, and evaluation of participants' practical performance. The effectiveness of the training was evaluated quantitatively using pre-test and post-test instruments. The evaluation results demonstrated a substantial improvement in teachers' ability to use ChatGPT, increasing from 11% before the training to 100% after the training. Furthermore, for the statement